Education and Implementation of Safety Result of Hazard Identification and Risk Control with JSA and HIRRARC Methods - Dwi Rahmawati; Kresna Febriyanto; Ferry Fadzlul Rahman; Zulqa Putri Kinanti; M. Gazali Ramadani; Kurnia Reski Yus Saputri; Firmansyah Firmansyah; Pramudya Andre Wardana; Annisa Nurmalia Siregar; Angela Ice Santosa; Ferdi Darjani (ABDIMAYUDA: Indonesia Journal of Community Empowerment for Health, 2023)
Abstract. Occupational Safety and Health is a protective effort aimed at ensuring that the workforce and other people in the workplace/company are always safe and healthy, and so that every source of production can be used safely and efficiently. PT PLN UL PLTGU Tanjung Batu is a company engaged in power, gas and steam power plants. In this battery change activity in the battery room peaking area, the author chose to use the JSA (Job Safety Analysis) and HIRARC (Hazard Identification, Risk Assessment, and Risk Control) methods and collected data using interviews and observations of workers. The results of battery replacement activities (ACCU) at the motor control center (MMC) can be used for companies to follow up or repair in every work carried out, the risks and work steps that exist in the activity process can be minimized by using a control hierarchy of control in the form of elimination, substitution, engineering, administrative and PPE (Personal Protective Equipment).